High-strength and high-toughness food packaging film based on PE film substrate, preparation method and application thereof

By introducing biodegradable additives, nanoreinforced materials and photosensitive coating technology on the PE film substrate, the shortcomings of traditional plastic packaging materials in environmental degradability, mechanical properties and functionality are solved, and high-strength, high toughness and environmentally friendly food packaging films are achieved.

CN119735881APending Publication Date: 2025-04-01厦门富锦新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411610086.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Traditional plastic packaging materials have shortcomings in environmental degradability, mechanical properties and functionality, resulting in environmental pollution and short service life of packaging materials.

Method used

Using composite food packaging film based on PE film substrates, the mechanical, environmentally friendly and functional properties of the material are improved by introducing biodegradable additives (such as PLA), nanoreinforced materials (such as nanosilica and nanosilver) and photosensitive coating technologies.

Benefits of technology

It significantly improves the mechanical strength, toughness, biodegradability, barrier properties and antibacterial properties of the packaging film, meets the high requirements of modern food packaging, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735881A_ABST
    Figure CN119735881A_ABST
Patent Text Reader

Abstract

The present invention provides a high-strength and high-toughness food packaging film based on a PE film substrate, a preparation method and application thereof, which significantly improves the mechanical properties (such as tensile strength and elongation at break), environmental performance (such as biodegradation rate) and functionality (such as barrier performance, antibacterial performance and weather resistance) of the packaging film by introducing biodegradable additives, nano-enhanced materials and photosensitive coating technology. It is suitable for packaging frozen foods, dried fruits, snacks, etc., and has excellent comprehensive performance and environmental protection characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PE packaging films, in particular to a high-strength and high-toughness food packaging film based on a PE film substrate, and a preparation method and application thereof. Background Art

[0002] With the continuous growth of the global population and the improvement of living standards, the demand for food packaging is increasing. Traditional plastic packaging materials, such as polyethylene (PE) and polypropylene (PP), are widely used in the field of food packaging due to their excellent mechanical properties and low cost. However, these traditional plastic materials have some significant problems that limit their widespread application and development: First, traditional plastic packaging materials are difficult to degrade in the natural environment, causing serious environmental pollution. Large amounts of plastic waste are piled up on land and in the ocean, causing damage to the ecosystem and affecting the survival of plants and animals.

[0003] Secondly, although traditional plastic materials have good mechanical properties, their mechanical strength and toughness will decrease significantly in certain special applications (such as high temperature and high humidity environments), affecting the service life and safety of packaging materials.

[0004] In addition, traditional plastic packaging materials mainly focus on mechanical properties and costs, lack multifunctional properties such as antibacterial, moisture-proof, and antioxidant properties, and cannot meet the high requirements of modern food packaging for safety and freshness.

[0005] In particular, with the increasingly stringent environmental protection regulations, more and more countries and regions have begun to restrict or ban the use of non-degradable plastic packaging materials, which has promoted the research and development and application of biodegradable materials.

[0006] In order to solve the above problems, in recent years, researchers and enterprises have been committed to developing new high-performance food packaging materials. Among them, biodegradable materials, nano-enhancement technology and photosensitive coating technology have received widespread attention: 1. Biodegradable materials: such as polylactic acid (PLA), starch, etc. These materials can be decomposed by microorganisms in the natural environment, reducing pollution to the environment. However, the mechanical properties of pure biodegradable materials are usually poor, which limits their application in high-strength packaging.

[0007] 2. Nano-enhancement technology: By adding nano-scale fillers (such as nano-silicon dioxide, nano-clay, nano-silver, etc.) to the polymer matrix, the mechanical strength, toughness and barrier properties of the material can be significantly improved. The introduction of nanomaterials also gives the packaging material multifunctional properties such as antibacterial and moisture-proof.

[0008] 3. Photosensitive coating technology: By coating a layer of photosensitive material on the surface of the plastic film, a chemical reaction can occur under light of a specific wavelength, further enhancing the mechanical properties of the material or initiating the degradation process. Photosensitive coating can also improve the weather resistance and surface properties of the material.

[0009] In summary, the development of a composite food packaging film with biodegradability, nano-enhancement and photosensitive coating can not only solve the environmental problems of traditional plastic packaging materials, but also significantly improve the mechanical properties and functionality of packaging materials to meet the high requirements of modern food packaging.

[0010] In view of this, the inventors specially designed a high-strength and high-toughness food packaging film based on a PE film substrate, a preparation method and application thereof, and this case was thus generated. Summary of the invention

[0011] In order to solve the above problems, one of the technical solutions of the present invention is as follows: The high-strength and high-toughness food packaging film based on PE film substrate includes an outer layer, a middle layer and an inner layer, wherein: The outer layer comprises the following components: Low-density polyethylene (LDPE), 30wt% to 34wt%; Fluoropolymer, 0.5wt%~0.7wt%; Metallocene linear low-density polyethylene (mLLDPE), 59wt% to 63wt%; Biodegradable additives (such as PLA), 2wt% to 4wt%; Nano silicon dioxide, 1wt% to 2wt%; Antioxidant, 0.1wt%~0.3wt%; Light stabilizer, 0.1wt%~0.3wt%; Photosensitive coating precursor, 1wt%~2wt%; The middle layer comprises the following components: Low-density polyethylene (LDPE), 10wt% to 15wt%; Linear low-density polyethylene (LLDPE), 35wt% to 40wt%; Fluoropolymer, 0.5wt%~0.8wt%; Metallocene linear low-density polyethylene (mLLDPE), 33wt% to 38wt%; Biodegradable additives (such as PLA), 5wt% to 8wt%; Nanoclay, 1wt%~2wt%; Antioxidant, 0.1wt%~0.3wt%; Light stabilizer, 0.1wt%~0.3wt%; Antimicrobial agent, 1wt% to 2wt%; The inner layer comprises the following components: Low-density polyethylene (LDPE): 8wt%~11wt%; Linear low-density polyethylene (LLDPE): 55wt%~59wt%; Fluoropolymer: 0.5wt%~0.7wt%; Metallocene linear low-density polyethylene (mLLDPE): 24wt%~27wt%; Biodegradable additives (such as PLA): 3wt%~5wt%; Nanosilver: 0.5wt%~1wt%; Antioxidant: 0.1wt%~0.3wt%; Light stabilizer: 0.1wt%~0.3wt%; Moisture-proof agent: 1wt%~2wt%.

[0012] Preferably, the biodegradable additive is polylactic acid.

[0013] Preferably, the nano-reinforcement material includes nano-silicon dioxide and nano-clay.

[0014] Preferably, the antibacterial agent is nanosilver.

[0015] Preferably, the photosensitive coating precursor comprises a photosensitive resin and a photoinitiator, wherein the photosensitive resin is an acrylate and the photoinitiator is benzophenone.

[0016] The second technical solution of the present invention is as follows: A method for preparing a food packaging film comprises the following steps: Step 1: Mixing and modification: Weigh each component of the formula; Place all components in a high-speed mixer and mix at 1000 rpm for 10 minutes to ensure that all components are fully mixed; The mixed materials were added into a twin-screw extruder, and the extrusion temperature was set to 180°C to 220°C and the screw speed was set to 300 rpm to extrude modified PE particles; Step 2: Biaxial stretching: The modified PE particles are made into films by blow molding or casting process, and the thickness is controlled between 20μm and 50μm; The film was stretched using a biaxial stretching device, with the stretching ratio set to 3:1, the stretching temperature to 100°C to 120°C, and the stretching speed to 20% / min; Step 3: Surface treatment: The film surface was modified using a plasma treatment device, with the power set to 100 W and the treatment time to 1 minute; Alternatively, the film may be immersed in a solution containing a modifier for 5 minutes using a chemical plating method and then dried naturally; Step 4: Coating application: Prepare photosensitive coating solution: photosensitive resin 50wt%, photoinitiator 5wt%, solvent 45wt%; Use a spraying device to evenly spray the photosensitive coating solution on the surface of the film, and the coating thickness is controlled at 1μm to 2μm; The sprayed film was placed in an oven, the temperature was set to 120°C, and the drying time was 5 minutes to completely cure the coating.

[0017] Preferably, the stretching temperature of the biaxial stretching equipment is 110°C and the stretching speed is 20% / min.

[0018] Preferably, the power of the plasma processing equipment is 100 W and the processing time is 1 minute.

[0019] Preferably, the solvent of the photosensitive coating solution is ethanol, and the film after spraying is dried at 120° C. for 5 minutes.

[0020] The third technical solution of the present invention is as follows: The invention discloses an application of a food packaging film in food packaging, which is used for packaging frozen food, dried fruit or snacks.

[0021] The present invention significantly improves the mechanical properties, environmental performance and functionality of the packaging film by introducing biodegradable additives, nano-enhanced materials and photosensitive coating technology, and is suitable for various food packaging, especially food that needs to be stored for a long time and transported over long distances. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings described herein are used to provide further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0023] in: Figure 1 It is a schematic diagram of the film structure of the present invention; Figure 2 is a graph of biodegradability test results in the present invention; Figure 3 is a graph of tensile strength test results in the present invention; Figure 4 is a graph of elongation at break test results in the present invention; Figure 5is a graph of oxygen permeability test results in the present invention; Figure 6 is a water vapor transmission rate test result chart of the present invention; Figure 7 is a graph of antibacterial test results in the present invention; Figure 8 is a coating adhesion test result chart in the present invention; Fig. 9 It is a chart showing the test results of the ultraviolet aging performance in the present invention. DETAILED DESCRIPTION

[0024] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Example

[0025] Combination Figure 1-9 Preparation of outer layer material formula: Low-density polyethylene (LDPE): 32wt% Fluoropolymer: 0.6wt% Metallocene linear low-density polyethylene (mLLDPE): 61wt% Biodegradable additive (PLA): 3wt% Nano-silicon dioxide: 1.5wt% Antioxidant: 0.2wt% Light stabilizer: 0.2wt% Photosensitive coating precursor: 1.5wt% Preparation steps: Weigh each component according to the above formula.

[0026] Place all components in a high-speed mixer and mix at 1000 rpm for 10 minutes to ensure that all components are fully mixed.

[0027] The mixed materials were added into a twin-screw extruder, and the extrusion temperature was set to 200°C and the screw speed to 300 rpm to extrude modified PE particles.

[0028] Preparation of middle layer material formula: Low-density polyethylene (LDPE): 12wt% Linear low-density polyethylene (LLDPE): 37wt% Fluoropolymer: 0.6wt% Metallocene linear low-density polyethylene (mLLDPE): 35wt% Biodegradable additive (PLA): 6wt% Nanoclay: 1.5wt% Antioxidant: 0.2wt% Light stabilizer: 0.2wt% Antimicrobial agent: 1.5wt% Preparation steps: Weigh each component according to the above formula.

[0029] Place all components in a high-speed mixer and mix at 1000 rpm for 10 minutes to ensure that all components are fully mixed.

[0030] The mixed materials were added into a twin-screw extruder, and the extrusion temperature was set to 200°C and the screw speed to 300 rpm to extrude modified PE particles.

[0031] Preparation of inner layer material formula: Low-density polyethylene (LDPE): 9.5wt% Linear low-density polyethylene (LLDPE): 57wt% Fluoropolymer: 0.6wt% Metallocene linear low-density polyethylene (mLLDPE): 25.5wt% Biodegradable additive (PLA): 4wt% Nanosilver: 0.8wt% Antioxidant: 0.2wt% Light stabilizer: 0.2wt% Moisture-proof agent: 1.2wt% Preparation steps: Weigh each component according to the above formula.

[0032] Place all components in a high-speed mixer and mix at 1000 rpm for 10 minutes to ensure that all components are fully mixed.

[0033] The mixed materials were added into a twin-screw extruder, and the extrusion temperature was set to 200°C and the screw speed to 300 rpm to extrude modified PE particles.

[0034] Preparation of composite membranes Biaxial stretch forming: The modified PE particles prepared above are made into films by blow molding or casting process, and the thickness is controlled at 30 μm.

[0035] The film was stretched using a biaxial stretching device with a stretching ratio of 3:1, a stretching temperature of 110°C, and a stretching speed of 20% / min.

[0036] Surface treatment: The film surface was modified using a plasma treatment device, with the power set to 100 W and the treatment time set to 1 minute.

[0037] Alternatively, a chemical plating method is used, where the film is immersed in a solution containing the modifier for 5 minutes and then dried naturally.

[0038] Coating application: Prepare the photosensitive coating solution: photosensitive resin (acrylate) 50wt%, photoinitiator (benzophenone) 5wt%, solvent (ethanol) 45wt%.

[0039] The photosensitive coating solution was evenly sprayed on the film surface using a spraying device, and the coating thickness was controlled at 1.5 μm.

[0040] The sprayed film was placed in an oven, the temperature was set to 120°C, and the drying time was 5 minutes to completely cure the coating.

[0041] Test items: tensile strength, elongation at break, tear strength Test method: Tested according to ASTM D882 standard Experimental groups: Control group: ordinary PE film Experimental Group 1: Low biodegradable additive (2wt% PLA) Experimental Group 2: Moderately biodegradable additive (3wt% PLA) Experimental Group 3: Highly biodegradable additive (4wt% PLA) Experimental Group 4: Low nano-reinforcement material (1wt% nano-silica) Experimental Group 5: Medium nano-reinforced material (1.5wt% nano-silica) Experimental Group 6: Highly nano-reinforced materials (2wt% nano-silica) Experimental Group 7: Low photosensitivity coating precursor (1wt%) Experimental Group 8: Medium photosensitive coating precursor (1.5wt%) Experimental Group 9: Highly photosensitive coating precursor (2wt%)

[0042] Test item: Biodegradation rate Test method: Tested according to ASTM D6400 Experimental groups: Control group: ordinary PE film Experimental Group 1: Low biodegradable additive (2wt% PLA) Experimental Group 2: Moderately biodegradable additive (3wt% PLA) Experimental Group 3: Highly biodegradable additive (4wt% PLA)

[0043] Test items: oxygen permeability, water vapor permeability Test method: Tested in accordance with ASTM D3985 and ASTM E96 standards Experimental groups: Control group: ordinary PE film Experimental Group 1: Low nano-reinforcement material (1wt% nano-silica) Experimental Group 2: Medium nano-reinforcement material (1.5wt% nano-silica) Experimental Group 3: Highly nano-reinforced materials (2wt% nano-silica)

[0044] Test item: Antibacterial effect Test method: Tested in accordance with ISO 22196 standard Experimental groups: Control group: ordinary PE film Experimental group 1: low antimicrobial agent (1wt%) Experimental Group 2: Medium antimicrobial agent (1.5wt%) Experimental Group 3: High antimicrobial agent (2wt%)

[0045] Test items: Weather resistance and mechanical properties of photosensitive coatings Test methods: UV aging test (according to ASTM G154 standard), coating adhesion test (according to ASTMD3359 standard) Experimental groups: Control group: ordinary PE film Experimental Group 1: Low photosensitivity coating precursor (1wt%) Experimental Group 2: Medium photosensitive coating precursor (1.5wt%) Experimental Group 3: Highly photosensitive coating precursor (2wt%) Analysis shows that:

[0046] Tensile strength: With the increase of biodegradable additives (PLA) and nano-reinforcement materials (nano-silica), the tensile strength gradually increased. For example, the tensile strength of experimental group 3 (4wt% PLA) reached 26 MPa, which was 30% higher than that of the control group (20 MPa). The addition of nano-reinforcement materials further increased the tensile strength, and the tensile strength of experimental group 6 (2wt% nano-silica) reached 27 MPa.

[0047] Elongation at break: The addition of biodegradable additives and nano-reinforcements significantly increased the elongation at break. For example, the elongation at break of experimental group 3 (4wt% PLA) reached 360%, a 20% increase over the control group (300%). The addition of nano-reinforcements further increased the elongation at break, with the elongation at break of experimental group 6 (2wt% nano-silica) reaching 360%.

[0048] Tear strength: The addition of biodegradable additives and nano-reinforcements significantly increased the tear strength. For example, the tear strength of experimental group 3 (4wt% PLA) reached 110 N / mm, which was 37.5% higher than that of the control group (80 N / mm). The addition of nano-reinforcements further increased the tear strength, and the tear strength of experimental group 6 (2wt% nano-silica) reached 110 N / mm.

[0049] In principle, PLA is a biodegradable polymer with good flexibility and mechanical properties. Adding PLA can improve the flexibility and elongation at break of the composite film.

[0050] Nano-silica has a high specific surface area and high activity, and can form a strong interaction with the polymer substrate to improve the mechanical strength and toughness of the composite film.

[0051] Biodegradation rate: As the content of biodegradable additive (PLA) increases, the biodegradation rate increases significantly. For example, the biodegradation rate of experimental group 3 (4wt% PLA) reaches 70%, which is 70% higher than that of the control group (0%).

[0052] In principle, PLA is a polymer that can be degraded by microorganisms. Adding PLA can significantly improve the biodegradability of the composite film and reduce pollution to the environment.

[0053] Oxygen transmission rate: As the content of nano-reinforced materials (nano-silica) increases, the oxygen transmission rate decreases significantly. For example, the oxygen transmission rate of experimental group 3 (2wt% nano-silica) dropped to 8 cm³ / m²·day·atm, which is 46.7% lower than that of the control group (15 cm³ / m²·day·atm).

[0054] Water vapor transmission rate: As the content of nano-reinforced material (nano-silica) increases, the water vapor transmission rate decreases significantly. For example, the water vapor transmission rate of experimental group 3 (2wt% nano-silica) dropped to 0.8 g / m²·day, which is 60% lower than that of the control group (2 g / m²·day).

[0055] The principle is that nano-silicon dioxide has high barrier properties and can fill the pores in the polymer matrix, reducing the permeation of gas and water molecules, thereby improving the barrier properties of the composite film.

[0056] Antibacterial rate: As the content of antibacterial agents (such as nanosilver) increases, the antibacterial rate increases significantly. For example, the antibacterial rate of experimental group 3 (2wt% antibacterial agent) reaches 99%, which is 99% higher than that of the control group (0%).

[0057] In principle, nanosilver has broad-spectrum antibacterial properties and can destroy bacterial cell walls by releasing silver ions, thereby killing or inhibiting the growth of bacteria.

[0058] Coating adhesion: With the increase of photosensitive coating precursor content, the coating adhesion is significantly improved. For example, the coating adhesion of experimental group 3 (2wt% photosensitive coating precursor) reaches 5B, which is 100% higher than that of the control group (0B).

[0059] Performance degradation rate after UV aging: As the content of photosensitive coating precursor increases, the performance degradation rate after UV aging decreases significantly. For example, the performance degradation rate after UV aging of experimental group 3 (2wt% photosensitive coating precursor) dropped to 5%, which is 75% lower than that of the control group (20%).

[0060] The principle is that the photosensitive coating precursor will undergo a chemical reaction under light of a specific wavelength to form a stable cross-linked structure, which improves the adhesion and weather resistance of the coating and reduces the impact of UV aging on material properties.

[0061] In summary, the present invention provides a high-strength and high-toughness food packaging film based on a PE film substrate and a preparation method thereof. By introducing biodegradable additives, nano-enhanced materials and photosensitive coating technology, the mechanical properties, environmental performance and functionality of the packaging film are significantly improved, providing a new development direction for the food packaging industry. Experimental data show that the composite film of the present invention exhibits significant advantages in mechanical properties, biodegradability, barrier properties, antibacterial properties and photosensitive coating properties, and has broad application prospects.

[0062] The present invention is described above by way of example in conjunction with the accompanying drawings. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned method. As long as various non-substantial improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A high-strength and high-toughness food packaging film based on a PE film substrate, characterized in that: It includes outer layer, middle layer and inner layer, among which: The outer layer comprises the following components: Low-density polyethylene (LDPE), 30wt% to 34wt%; Fluoropolymer, 0.5wt%~0.7wt%; Metallocene linear low-density polyethylene (mLLDPE), 59wt% to 63wt%; Biodegradable additives (such as PLA), 2wt% to 4wt%; Nano silicon dioxide, 1wt% to 2wt%; Antioxidant, 0.1wt%~0.3wt%; Light stabilizer, 0.1wt%~0.3wt%; Photosensitive coating precursor, 1wt%~2wt%; The middle layer comprises the following components: Low-density polyethylene (LDPE), 10wt% to 15wt%; Linear low-density polyethylene (LLDPE), 35wt% to 40wt%; Fluoropolymer, 0.5wt%~0.8wt%; Metallocene linear low-density polyethylene (mLLDPE), 33wt% to 38wt%; Biodegradable additives (such as PLA), 5wt% to 8wt%; Nanoclay, 1wt%~2wt%; Antioxidant, 0.1wt%~0.3wt%; Light stabilizer, 0.1wt%~0.3wt%; Antimicrobial agent, 1wt% to 2wt%; The inner layer comprises the following components: Low-density polyethylene (LDPE): 8wt%~11wt%; Linear low-density polyethylene (LLDPE): 55wt%~59wt%; Fluoropolymer: 0.5wt%~0.7wt%; Metallocene linear low-density polyethylene (mLLDPE): 24wt%~27wt%; Biodegradable additives (such as PLA): 3wt%~5wt%; Nanosilver: 0.5wt%~1wt%; Antioxidant: 0.1wt%~0.3wt%; Light stabilizer: 0.1wt%~0.3wt%; Moisture-proof agent: 1wt%~2wt%.

2. The high-strength and high-toughness food packaging film based on a PE film substrate according to claim 1, characterized in that: The biodegradable additive is polylactic acid.

3. The high-strength and high-toughness food packaging film based on a PE film substrate according to claim 1, characterized in that: The nano-enhanced material includes nano-silicon dioxide and nano-clay.

4. The high-strength and high-toughness food packaging film based on a PE film substrate according to claim 1, characterized in that: The antibacterial agent is nano silver.

5. The high-strength and high-toughness food packaging film based on a PE film substrate according to claim 1, characterized in that: The photosensitive coating precursor comprises a photosensitive resin and a photoinitiator, wherein the photosensitive resin is an acrylate and the photoinitiator is benzophenone.

6. A method for preparing the food packaging film according to claim 1, characterized in that: The following steps are involved: Step 1: Mixing and modification: Weigh each component according to the formula of claim 1; Place all components in a high-speed mixer and mix at 1000 rpm for 10 minutes to ensure that all components are fully mixed; The mixed materials were added into a twin-screw extruder, and the extrusion temperature was set to 180°C to 220°C and the screw speed was set to 300 rpm to extrude modified PE particles; Step 2: Biaxial stretching: The modified PE particles are made into films by blow molding or casting process, and the thickness is controlled between 20μm and 50μm; The film was stretched using a biaxial stretching device, with the stretching ratio set to 3:1, the stretching temperature to 100°C to 120°C, and the stretching speed to 20% / min; Step 3: Surface treatment: The film surface was modified using a plasma treatment device, with the power set to 100 W and the treatment time to 1 minute; Alternatively, the film may be immersed in a solution containing a modifier for 5 minutes using a chemical plating method and then dried naturally; Step 4: Coating application: Prepare photosensitive coating solution: photosensitive resin 50wt%, photoinitiator 5wt%, solvent 45wt%; Use a spraying device to evenly spray the photosensitive coating solution on the surface of the film, and the coating thickness is controlled at 1μm to 2μm; The sprayed film was placed in an oven, the temperature was set to 120°C, and the drying time was 5 minutes to completely cure the coating.

7. The preparation method according to claim 6, characterized in that: The stretching temperature of the biaxial stretching equipment is 110°C and the stretching speed is 20% / min.

8. The preparation method according to claim 6, characterized in that: The power of the plasma treatment equipment is 100 W, and the treatment time is 1 minute.

9. The preparation method according to claim 6, characterized in that: The solvent of the photosensitive coating solution is ethanol, and the film after spraying is dried at 120° C. for 5 minutes.

10. Use of the food packaging film according to claim 1 in food packaging, characterized in that: For packaging frozen foods, dried fruits or snacks.